Comparative Evaluation of Fluoride Uptake Rate in the Enamel of Primary Teeth after Application of Two Pediatric Dentifrices - B. Malekafzali; N. Tadayon (Tehran University of Medical Sciences, 2006)
Statement of problem: The effectiveness of fluoride dentifrices in reducing dental caries is well documented. However, not all fluoride dentifrices are equally effective Purpose: The objective of this experimental study was to compare fluoride uptake from Pooneh pediatric toothpaste and an ADA-approved pediatric dentifrice, in sound enamel of primary teeth. Materials and Methods: In an in vitro randomized controlled trial, 20 sound primary canines were divided into 2 groups according to the experimental dentifrices. Each tooth was sectioned longitudinally into experimental and control halves. The test groups were treated with dentifrice slurries for 1 hour. All specimens were then suspended in 5ml artificial saliva for 24 hours at 37˚C and were etched twice for 30 seconds with a 1ml solution of 0.5M percholoric acid. Fluoride and calcium concentrations were measured by a potentiometer and an atomic absorption spectrophotometer, respectively. The collected data were analyzed using repeated measurement ANOVA and Tukey's test. Results: The mean fluoride concentrations in the Aqua fresh group (4098.44 and 3755.25 ppm in first and both layers respectively) were higher than Pooneh (first layer 2420.51 ppm and both layers 2242.73 ppm), and both were higher than the controls (P